2016
DOI: 10.1002/hon.2302
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and epidemiology of non‐Hodgkin lymphoma and risk of second malignancy among 22 466 survivors in Israel with 30 years of follow‐up

Abstract: Previous studies have shown an increase risk of second malignancies after non-Hodgkin's lymphoma (NHL), which is probably related to a combination of factors including genetic predisposition, molecular background, host immunological status and therapy administered. Here, we determined the incidence of NHL and risk of second solid tumours and haematological malignancies among survivors of NHL diagnosed in Israel during 1980-2011. Data were collected from the records of the Israeli National Cancer Registry. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The excess risk of SPM in NHL demonstrated in our study is in line with previous literature, although prior studies vary in terms of design and sources of the study populations and most often lack data regarding subtypes [4][5][6][7][8][9][10][11][12][13][14] . In a 2011 meta-analysis Pirani et al found pooled relative risks of 1.88 for any secondary cancer, and relative risk of 1.32 for solid tumors among patients with NHL 11 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The excess risk of SPM in NHL demonstrated in our study is in line with previous literature, although prior studies vary in terms of design and sources of the study populations and most often lack data regarding subtypes [4][5][6][7][8][9][10][11][12][13][14] . In a 2011 meta-analysis Pirani et al found pooled relative risks of 1.88 for any secondary cancer, and relative risk of 1.32 for solid tumors among patients with NHL 11 .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have consistently shown increased risks of SPM in general, and of myeloid malignancies in particular [4][5][6][7][8][9][10][11][12][13][14] . However, many of these studies have not investigated the most recent time periods with modern treatments, and have included small, sometimes selected, patient groups.…”
Section: Introductionmentioning
confidence: 99%
“…When we chose SPM, we did not include some important parts, including the head and neck. And these are considered to be the location of SPM, and some are often fatal (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hematologic malignancies treated with chemotherapy have increased risk of developing LPDs [6,7], being CLL/SLL the most frequently observed entity in these patients. Notably, patients treated with fludarabine appear to have a high predisposition for developing CR-LPDs with DLBCL accounting for the most common type of CR-LPDs arising in these cases, followed by polymorphic LPDs, and CHL [8].…”
Section: Discussionmentioning
confidence: 99%